2021
DOI: 10.3389/fpsyg.2021.611155
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Evidence on the Role of Digital Technology in Shaping Attention and Cognitive Control in Children

Abstract: The role of digital technology in shaping attention and cognitive development has been at the centre of public discourse for decades. The current review presents findings from three main bodies of literature on the implications of technology use for attention and cognitive control: television, video games, and digital multitasking. The aim is to identify key lessons from prior research that are relevant for the current generation of digital users. In particular, the lack of scientific consensus on whether digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 237 publications
1
35
0
1
Order By: Relevance
“…This study’s aim was to further characterize processes of feature binding and response selection in the context of TEC by providing a more profound understanding of the neurophysiological correlates accompanying the development of these mechanisms from late childhood to early adulthood. Mechanisms underlying processes of binding stimulus and response features are of central importance in the context of developmental cognitive neuroscience, because cognitive control processes are subject to strong developmental changes across childhood and young adulthood ( Friedman et al, 2009 ; Luna, 2009 ; Luna et al, 2010 ; Marek et al, 2015 ; Munakata et al, 2012 ; Vedechkina and Borgonovi, 2021 ) and a common theme that runs through all these lines of research in cognitive control is how stimulus input becomes associated with a particular response and how this association becomes represented ( Freund et al, 2021 ). The TEC framework represents one important theoretical framework addressing this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study’s aim was to further characterize processes of feature binding and response selection in the context of TEC by providing a more profound understanding of the neurophysiological correlates accompanying the development of these mechanisms from late childhood to early adulthood. Mechanisms underlying processes of binding stimulus and response features are of central importance in the context of developmental cognitive neuroscience, because cognitive control processes are subject to strong developmental changes across childhood and young adulthood ( Friedman et al, 2009 ; Luna, 2009 ; Luna et al, 2010 ; Marek et al, 2015 ; Munakata et al, 2012 ; Vedechkina and Borgonovi, 2021 ) and a common theme that runs through all these lines of research in cognitive control is how stimulus input becomes associated with a particular response and how this association becomes represented ( Freund et al, 2021 ). The TEC framework represents one important theoretical framework addressing this.…”
Section: Discussionmentioning
confidence: 99%
“…The term cognitive control can be regarded to be synonymous to executive functions ( Diamond, 2013 ), albeit there are nuances between these definitions ( Nigg, 2017 ) and multiple facets of cognitive control processes can be distinguished ( Diamond, 2013 ; Freund et al, 2021 ). Several lines of evidence suggest that that cognitive control processes are subject to profound developmental changes across childhood and young adulthood in typical populations (e.g., Friedman et al, 2009 ; Luna, 2009 ; Luna et al, 2010 ; Marek et al, 2015 ; Munakata et al, 2012 ; Vedechkina and Borgonovi, 2021 ), which are also of relevance for developmental neuropsychiatric disorders ( Arnsten and Rubia, 2012 ; McTeague et al, 2017 ; Nigg, 2017 ). However, a common theme that runs through all these lines of research is the tenet that cognitive control relates to the processes of translating a specific stimulus input to an appropriate behavioral output in a given task context.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study among adolescents showed that the higher the number of hours spent using technological devices, the lower life satisfaction ( 10 ). Additionally, exposure to screens has been related to poorer cognitive and academic functioning, including problems with attention ( 11 ), language ( 11 ), memory ( 12 ), learning ( 12 ), and visuospatial processing ( 7 ). Moreover, gaming addiction is a rising concern with a prevalence ranging from 2.0 to 3.1% among the young population worldwide ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was no effect on other EF skills like multitasking, switching, and working memory. The effect of video gaming on EF was not supported in reviews for studies with children [ 26 ] or elder samples [ 27 ].…”
Section: Introductionmentioning
confidence: 99%